IPAD-BASED ASSESSMENT IN PARKINSON'S DISEASE. Issue 11 (14th October 2015) - Noad, Rupert; Newman, Craig; Carroll, Camille; Zajicek, John
Abstract : Background: In order to facilitate neuroprotective trials in Parkinson's disease (PD), there is a need for improved means of early disease detection and measuring disease progression. Computerised assessment may afford easier and increasingly accurate administration of motor and cognitive tests, as well as measurement of indices not readily accessible with standard testing paradigms. Aim: To develop and validate iPad-based cognitive and motor measures in PD. Method: 62 PD patients and 42 age-matched controls completed traditional and iPad versions of the Trail Making Test (TMT) (executive function) and Knox Cube Test (visual memory), as well as a range of other measures. Results: Median age was 68 years; median MOCA score was 26. No participant had previously used an iPad. There was significant correlation between traditional and iPad measures: TMTa r=0.74, p<0.001; TMTb r=0.76, p<0.001; Knox r=0.63, p<0.001. Usability data were strong, 90% of participants providing positive feedback. Conclusion: This initial study has demonstrated that two iPad-based measures of cognition are acceptable to PD patients and perform similarly to traditional pen-and-paper tests. Further work will extend the analysis of the measured indices in longitudinal studies to determine correlation with disease progression, and extend the battery of iPad-based tests available for PD assessment.